2020
DOI: 10.1097/mjt.0000000000001182
|View full text |Cite
|
Sign up to set email alerts
|

Teriparatide for the Treatment of Medication-Related Osteonecrosis of the Jaw

Abstract: Medication-related osteonecrosis of the jaw (MRONJ) is a painful and intractable disease of the jaw that clinically presents as an area of ulceration with exposed necrotic bone. In severe cases, it can predispose to jaw fracture, skin fistula, or osteolysis extending beyond the region of the alveolar bone. No effective treatment has been established for this condition. Recently, teriparatide, a recombinant parathyroid hormone, and the only FDA-approved osteoanabolic drug for the treatment of glucocorticoid-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
3
0
2
Order By: Relevance
“…For instance, recent studies have shown that parathyroid hormone has an osteogenic-inducing function and can stimulate osteogenesis [28] . Recombinant parathyroid hormone1-34 (rhPTH1-34, commercial name teriparatide) has demonstrated remarkable clinical e cacy in MRONJ [29][30][31] . Therefore, rhPTH1-34 may be the therapeutic target for PNJ, although further research is required to con rm this hypothesis, opening up the possibility of teriparatide treatment for patients with PNJ.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent studies have shown that parathyroid hormone has an osteogenic-inducing function and can stimulate osteogenesis [28] . Recombinant parathyroid hormone1-34 (rhPTH1-34, commercial name teriparatide) has demonstrated remarkable clinical e cacy in MRONJ [29][30][31] . Therefore, rhPTH1-34 may be the therapeutic target for PNJ, although further research is required to con rm this hypothesis, opening up the possibility of teriparatide treatment for patients with PNJ.…”
Section: Discussionmentioning
confidence: 99%
“…Teriparatide acetate effectively reduces bone resorption and has shown promising results in phase 4 trials ( Leder, 2017 ). It has been successfully used for the treatment of BRONJ ( Chopra and Malhan, 2020 ; Dos Santos Ferreira et al, 2021 ; Kwon and Kim, 2016 ; Sim et al, 2020 ; Yu and Su, 2020 ), and reduced serum calcium levels and improved bone integrity in osteoporosis and hypoparathyroidism patients ( Gutierrez-Cerecedo et al, 2016 ; Satterwhite et al, 2010 ). Considering the variable efficacy and side effects in human patients, it will be important to carefully examine other osteoporosis-approved drugs (Denosumab, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…TA effectively reduces bone resorption and has shown promising results in phase 4 trials (Leder, 2017). TA has been successfully used for the treatment of BRONJ (Chopra and Malhan, 2020; Dos Santos Ferreira et al, 2021; Kwon and Kim, 2016; Sim et al, 2020; Yu and Su, 2020), and reduced serum calcium levels and improved bone integrity in osteoporosis and hypoparathyroidism patients (Gutierrez-Cerecedo et al, 2016; Satterwhite et al, 2010). Considering the variable efficacy and side effects in human patients, it will be important to carefully examine other osteoporosis-approved drugs (Denosumab, etc.)…”
Section: Discussionmentioning
confidence: 99%